Pragmatic Analysis On The Suggestion Utterances Conveyed By The Students Of Fourth Semester Of English Department Of UMS In The Speaking Class - Jayantri, Kecik; , Dra. Siti Zuhriah Ariatmi, M.Hum; , Agus Wijayanto, Ph.D (2014)
The aim of this study is to describe the pragmalinguistic forms used in the suggestion and to describe the differences of strategies suggestions both by fourth semester female and male students of English Department Muhammadiyah University in the speaking class 2011. This study uses descriptive qualitative method. The data are the written text of suggestion utterances used in the speaking class 2011. The data of both pragmalinguistic forms were analyzed by Martinez-Flor and the differences of strategies suggestions were analyzed by Martinez-Flor. The technique of data collection are observation in the speaking class, recording the data of using DCT, interview of the data, classifying suggestion the DCT of English Department of UMS. The research finding showed that there are eight kinds of suggestion utterance: direct performative verb, direct noun of suggestion, conventionalized forms possibility/probability, conventionalized forms should, conventionalized forms conditional, indirect impersonal, hints, and certain modals and semi-modals used in the speaking class.